Application of electrogastrogram in assessment of gastric motility in acute pancreatitis - Cai, Ying; Wang, Jinyun; Huang, Deqiang; Luo, Lingyu (Frontiers in Physiology, 2023)
Background: Electrogastrogram (EGG) can reflect gastric motility disorders in many diseases, but its application in acute pancreatitis (AP) has not been studied. Therefore, our study aimed to investigate the value of EGG in assessing the existence of gastric motility disorder in patients with AP and in predicting the severity of AP. Methods: Patients with AP admitted to the First Affiliated Hospital of Nanchang University from June 2020 to December 2020 were enrolled. Five EGG parameters (Percentage of normal gastric slow wave (PNGSW), main frequency, average frequency, percentage of gastric tachycardia (PGT), percentage of gastric bradycardia (PGB)) were collected. The receiver operating characteristic (ROC) curve was constructed to judge the predictive value of EGG parameters to AP severity.Results: The PNGSW in AP patients was significantly lower than that of the control group (P<0.05), and the PGB was higher in AP patients than that of the control group (P<0.05). The area under curve (AUC) of the PNGSW and the PGB in diagnosing nonmild acute pancreatitis (N-MAP) were 0.777 (95% CI: 0.676-0.877, P＜0.001) and 0.775 (95% CI: 0.670-0.879, P<0.001) respectively. After combining with C-reactive protein, the accuracy, sensitivity and specificity of predicting N-MAP were improved.Conclusion: EGG parameters can well reflect the gastric motility disorder of AP patients. The PNGSW and the PGB can be used to predict the occurrence of N-MAP.